Evolution of Myocardial Protection - Wagner, Robert; Fila, Petr; Gabbasov, Zufar; Maruyama, Junko; Maruyama, Kazuo; Nicovsky, Jiri; Nemec, Petr (Highlights on Medicine and Medical Science Vol. 7, 2021)
For the surgical field to be peaceful and bloodless, the majority of cardiac surgery patients are operated on using the cardioprotective technique called ischaemic cardioplegic arrest. The current myocardial protection relies on the hyperkalaemic arrest, reinforced with hypothermia, a number of additives and mixing the cardioplegic solution with the patient’s blood. Cardiac surgery patients are now more risky in terms of age, comorbidities and the need for complex procedures. These groups of patients have a higher incidence of postprocedural complications and mortality. One factor to consider involves the current limits of intraoperative cardioplegia. It brings about reperfusion injury, which leads to dysfunction and/or loss of part of the myocardium. Also in the cardiology, acute myocardium infarction patients treated with contemporary mechanical revascularization principles, going onto develop post-infarct heart failure, which is now on the rise. Thus it is obvious that any reduction of periprocedural myocardial injury is important for the prognosis of the patient. One way of augmenting myocardial protection is the phenomenon of ischaemic conditioning, elicited with brief non-lethal episodes of ischaemia-reperfusion. In addition, drugs are being tested (and attracting great attention) that mimic ischaemic conditioning. Such cardioprotective techniques are mainly focused on reperfusion injury, a complex response of the organism to the restoration of coronary blood flow in ischaemic tissue, that can eventually lead to cell death. Extensive research over the last three decades has revealed the basic mechanisms of reperfusion injury and myocardial conditioning, suggesting its therapeutic potential. But despite the enormous efforts and resources that have been expended in preclinical studies, almost all cardioprotective therapies have failed in the third phase of clinical trials. One reason is that evolutionary young cellular mechanisms of protection against oxygen handling are not very robust. Ischaemic conditioning, which is among these, is also limited by this. At present, the prevailing belief is that such options of treatment exist, but their full employment will not occur until subquestions and methodological issues with the transfer into clinical practice have been resolved.